4 - Droit d’accès à l’internet et ordre public électoral en Afrique : la crédibilisation institutionnelle au Congo-Kinshasa à l’épreuve de la surveillance e-citoyenne - Bira’Mbovote, Jacques Kambale (Africa Development, 2022)
The electoral process in Africa continues to surprise many observers. One of the latest innovations of the current powers is to untimely disconnection of the internet before, during or after the elections. Hence the question at the centre of the debate: can electoral public order justify the restriction of the right to access internet? To answer this question, the December 2018 coupled elections in Congo-Kinshasa were the focus of this study. Thus, during this period, two approaches emerged. The statist approach, based on the monopoly of constraint with its philosophical presuppositions of hierarchy, order and normativity from above, and linked to the dual colonial and dictatorial past of Lumumba's country, is based on the reason of State under the guise of public order, which tends to block citizen intervention on the public scene. On the other hand, the egalitarian model, led by human rights defenders and citizen movement activists, relies on the sacredness and fundamental nature of the right to access internet, an essential component of the right to information and freedom of expression. In a systemic and historical approach, our analysis leads to an 'in-between' model: the contractualist model, which marries public order with the democratic requirements of e-citizen monitoring of the electoral process.